The Business Trip - Garcia, Jessie, 1970- (New York : St. Martin's Press, 2025)
""A stunning and accomplished debut, with hugely relatable characters and an addictive storyline that kept me turning the pages well into the night. Bravo!" --BA Paris, NYT bestselling author "Wow, The Business Trip was nonstop twists and turns. I loved the unusual way that the story was told, and I kept reading all day long because I couldn't wait to see how it ended!" -- Freida McFadden, NYT bestselling author THE BUSINESS TRIP is the gripping, page-turning debut from author Jessie Garcia. Stephanie and Jasmine have nothing and everything in common. The two women don't know each other but are on the same plane. Stephanie is on a business trip and Jasmine is fleeing an abusive relationship. After a few days, they text their friends the same exact messages about the same man-the messages becoming stranger and more erratic. And then the two women vanish. The texts go silent, the red flags go up, and the panic sets in. When Stephanie and Jasmine are each declared missing and in danger, it begs the questions: Who is Trent McCarthy? What did he do to these women- or what did they do to him? Twist upon twist, layer upon layer, where nothing is as it seems, The Business Trip takes you on a descent into the depths of a mastermind manipulator. But who is playing who?"--.
new book 2025 winter.
Keywords: Air travel; Missing persons; Man-woman relationships; Airplanes; Text messaging (Cell phone systems); FICTION / Thrillers; Novels; Thriller fiction